The problems of the choice of the most expedient form of codification of the norms of international private law - Вишновецька, С. В.; Ющенко, К. В. (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In the article are determined the advantages of «autonomous» codification of the norms of internationalprivate law. The authors give a conclusion that the most expedient form of codification of the norms of internationalprivate law is its fixing in the separate law.